Analysis and design of an adaptive-supply class H audio power amplifier for mobile devices - Zhang, Xiang (2017)
In recent years, the market of consumer electronics has witnessed a growing demand for portable devices with high-fidelity audio playback functionality. For battery-powered devices like smart phones, smart watches and tablets, their form factor as well as weight keep on shrinking to enable the good portability required by the customers. As a result, the board space left for the battery is likely to be further reduced. On the other hand, more functional blocks are expected to be integrated into the system which will deplete the battery even more quickly. Therefore, low quiescent power and high power efficiency have become key performance metrics for audio amplifiers designed for portable applications.